IMPLEMENTASI PENDIDIKAN BERBASIS RELIGI DAN ALAM DALAM MEMFASILITASI PEMBELAJARAN HOLISTIK DI KELAS III SD TAHFIZH QUR’AN MARDHATILLAH - Dwi Dipta Dalilah; Sholeh Hidayat; Istinganatul Ngulwiyah (Jurnal Pendidikan Dasar, 2025)
This study aims to determine how the implementation of religious and nature-based education facilitates holistic learning in grade III of Mardhatillah Tahfizh Qur'an Elementary School. The research method uses qualitative research with a descriptive type. The researcher took research sources consisting of the principal, class teachers and class III guidance teachers. Data were obtained through interviews, observations and documentation. The results of the study indicate that the basis for implementing religious and nature-based education consists of aspects of the curriculum foundation, teaching staff and students, as well as supervision and relationships with the outside community. Aspects of the process of implementing religious and nature-based education activities in facilitating holistic learning in grade III are contained in intracurricular, extracurricular and co-curricular activities using a religious and nature approach in each activity, as well as aspects of supporting and inhibiting factors for this education lie in teacher supervision and guidance, supporting activities, relationships with the community, facilities and infrastructure and student character.